An ultrahigh strength and enhanced ductility cold-rolled medium-Mn steel treated by intercritical annealing. (September 2018) - Li, Xuan; Song, Renbo; Zhou, Naipeng; Li, Jiajia
Abstract: An ultrahigh strength and enhanced ductility cold-rolled medium-Mn steel was manufactured via intercritical annealing. The fine lamellar and equiaxed duplex microstructure, austenite (40.5 vol%) and ferrite, was observed due to austenite reversed transformation and ferrite recrystallization. The ultimate tensile strength (1090.0 MPa), total elongation (56.3%) and product of strength and elongation (PSE) (61.4 GPa·%) were achieved, which were comparable and superior to the reported medium-Mn steels. The excellent properties were attributed to high dislocation density, transformation induced plasticity, twinning induced plasticity, grain refinement strengthening and solution strengthening effects. Additionally, the dependence of PSE on austenite fraction was discussed. Graphical abstract: Unlabelled Image